PENGATURAN HAK WARIS ANAK ANGKAT DALAM MASYARAKAT ADAT KASEPUHAN SINAR RESMI BERDASARKAN HUKUM ISLAM - Muhamad Budi Hermawan (INTELIGENSIA MEDIA, 2023)
Indigenous peoples in Indonesia recognize adoption. But the impact on inheritance can be different for each custom. The problem in this study is how to regulate the inheritance rights of adopted children in the official Kasepuhan Sinar Resmi based on Islamic law. The research method used is an empirical research method using primary data and secondary data. The results of the study stated that the arrangement of the inheritance rights of adopted children in the Kasepuhan Sinar Resmi based on Islamic law is that adopted children do not get inheritance rights. However, in the Kasepuhan Sinar Resmi indigenous people, the provisions regarding the granting of inheritance rights to adopted children use the provisions stipulated in the Compilation of Islamic Law, so that the inheritance rights of adopted children are given a mandatory will of up to 1/3 of the inheritance of their adoptive parents